The molecular approaches and challenges of Streptococcus pneumoniae serotyping for epidemiological surveillance in the vaccine era - Abdul Rahman, Nurul Asyikin; Mohd Desa, Mohd Nasir; Masri, Siti Norbaya; Taib, Niazlin Mohd; Sulaiman, Nurshahira; Hazman, Hazmin; John, James (Polish Society of Microbiologists, 2023)
Streptococcus pneumoniae (pneumococcus) belongs to the Gram-positive coccus category. This bacterium typically colonises the nasopharyngeal region of healthy individuals. It comprises an extremely distinct polysaccharide capsule adding to virulence, allowing the bacteria to elude the immune defence mechanisms. Consequently, it might trigger aggressive conditions like septicaemia and meningitis in immunocompromised or older individuals; moreover, children below five years of age, are at risk of morbidity and mortality. Studies have found 101 S. pneumoniae capsular serotypes, of which several correlate with clinical and carriage isolates with distinct disease aggressiveness. The introduction of pneumococcal conjugate vaccines (PCV) targets the most common disease-associated serotypes. Nevertheless, vaccine selection pressure leads to replacement of the formerly dominant vaccine serotypes (VTs) by non-vaccine types (NVTs). Therefore, serotyping must be conducted for epidemiological surveillance and vaccine assessment. Serotyping can be performed using numerous techniques either by the conventional antisera-based (Quellung and latex agglutination) or molecular based approaches (sequetyping, multiplex PCR, realtime PCR and PCR-RFLP). A cost-effective and practical approach must be used to enhance serotyping accuracy to monitor the prevalence of VTs and NVTs. Therefore, dependable pneumococcal serotyping techniques are essential to precisely monitor virulent lineages, NVT emergence, and genetic associations of isolates. This review discusses the principles, the associated benefits and drawbacks for the respective available conventional and molecular approaches, and potentially the whole genome sequencing (WGS) to be directed for future exploration.